(untitled) (International relations and international law Journal, 2016)
This article describes the brilliant idea of the Eurasian Union as it put forward by President N.A. Nazarbayev, penetrating into the consciousness of the people, becomes a material force; shows that the integration of the peoples and countries of Eurasia in the spirit of the modern age. In particular, this can be seen as a call to scientists dealing with the integration of peoples and countries of the world, and the Eurasian integration. The study of the idea of Eurasian integration should take place under the motto «Know yourself». The article also deals with the history of the emergence, development and the formation of Eurasianism, as by one of the ideological and political, social and economic phenomena of our time. Integration should be seen not only as the structure of the coordination of economic interests of the countries, but also as an alternative to war between the countries.